2020
DOI: 10.1021/acs.oprd.0c00326
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis in the Selection of Greener Solvents for the Bromination of 2-Cyano-4’-methylbiphenyl

Abstract: 4′-(Bromomethyl)-2-cyanobiphenyl (BCB) is a vital building block to various sartans, which are an important group of nonpeptide angiotensin II antagonists. The commercial manufacture of BCB from 2-cyano-4′-methylbiphenyl by Wohl−Ziegler bromination is, however, dependent on troublesome chlorinated solvents such as chlorobenzene or carbon tetrachloride. In this work, we use the response surface methodology (RSM) together with solvent principal components as an exploratory tool to identify greener solvent altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Delightfully, diethyl carbonate (DEC) gave a large improvement compared with EtOAc, whereas ethyl lactate did not work well. This observation for ethyl lactate was in accordance with results with alcohols in general in previous work, but remarkably, the yield in DEC was higher . Continuing with DEC, a trial at room temperature for 3 h (entry 23) confirmed that temperature does not seem important in the tested experimental space.…”
Section: Resultssupporting
confidence: 91%
“…Delightfully, diethyl carbonate (DEC) gave a large improvement compared with EtOAc, whereas ethyl lactate did not work well. This observation for ethyl lactate was in accordance with results with alcohols in general in previous work, but remarkably, the yield in DEC was higher . Continuing with DEC, a trial at room temperature for 3 h (entry 23) confirmed that temperature does not seem important in the tested experimental space.…”
Section: Resultssupporting
confidence: 91%
“…Acetone is an example that many guides classify as a recommended solvent, while AstraZeneca and GSK have labelled it as associated with issues due to impacted waste scores concerning VOC potential and biotreatment. 120,130,132 Common agreements within guides suggest that preferred solvents for pharmaceutical processes consist largely of alcohols and esters for example n-butanol and ethyl acetate, and water.…”
Section: How Can Researchers Be Informed About Their Solvent Choice?mentioning
confidence: 99%
“…The utilisation of PCA solvent maps allows optimisation of a reaction to be carried out by a design of experiment (DoE) approach rather than a more laborious one variable at a time (OVAT) strategy. 132,135 The availability and application of such selection tools and guides is highly benecial (Fig. 11).…”
Section: How Can Researchers Be Informed About Their Solvent Choice?mentioning
confidence: 99%